The pH acidity and nitrate accumulation by plasma discharge enhanced the growth and phytochemicals of soybean sprouts grown in reused water - Jong-Seok Song; Sunkyung Jung (Food Chemistry: X, 2024)
This study investigated the effect of plasma treatment on reused water and evaluated the interactions of the plasma-treated water (PTW) with plants or microbes to determine the optimal PTW for reuse. The repeated treatment gradually accumulated nitrate (NO3−) in the PTW and lowered its pH; afterward, it led to the sprouted soybeans accumulating other inorganic ions in the PTW. The biomass of soybean sprouts was enhanced by the accumulated NO3− but decreased due to the pH effect. Meanwhile, the acidic pH reduced the microbial counts, but they increased after sprinkling the PTW over the sprouts. The optimal PTW in our study, which had a gradual increase of NO3− (≤321.8 mg·L−1) with an acceptable pH (≥pH 3), significantly enhanced the biomass by 4.2% compared to the untreated control. Additionally, it increased the total content of amino acids and isoflavones by 9% and 18% in the growing part, respectively.